Firm dynamics, misallocation and targeted policies - In Hwan Jo; Tatsuro Senga (Queen Mary University of London, School of Economics and Finance, 2016)
Access to external finance is a major obstacle for small and young firms; thus, providing subsidized credit to small and young firms is a widely-used policy option across countries. We study the impact of such targeted policies on aggregate output and productivity and highlight indirect general equilibrium effects. To do so, we build a model of heterogeneous firms with endogenous entry and exit, wherein each firm may be subject to forward-looking collateral constraints for their external borrowing. Subsidized credit alleviates credit constraints small and young firms face, which helps them to achieve the efficient and larger scale of production. This direct effect is, however, either reinforced or offset by indirect general equilibrium effects. Factor prices increase as subsidized firm demand more capital and labor. As a result, higher production costs induce more unproductive incumbents to exit, while replacing them selectively with productive entrants. This cleansing effect reinforces the direct effect by enhancing the aggregate productivity. However, the number of firms in operation decreases in equilibrium, and this, in turn, depresses the aggregate productivity.
Keywords: E22; G32; O16; 330; Firm dynamics; Misallocation; Financial frictions; Firm size and age